2023
DOI: 10.1021/acs.jmedchem.2c01572
|View full text |Cite
|
Sign up to set email alerts
|

A Medicinal Chemistry Perspective on Excitatory Amino Acid Transporter 2 Dysfunction in Neurodegenerative Diseases

Abstract: The excitatory amino acid transporter 2 (EAAT2) plays a key role in the clearance and recycling of glutamate - the major excitatory neurotransmitter in the mammalian brain. EAAT2 loss/dysfunction triggers a cascade of neurodegenerative events, comprising glutamatergic excitotoxicity and neuronal death. Nevertheless, our current knowledge regarding EAAT2 in neurodegenerative diseases, such as amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (AD), is restricted to post-mortem analysis of brain tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 191 publications
4
7
0
Order By: Relevance
“…Immunofluorescence staining showed abundant co-localization of GLT1 with GFAP in the control group, indicating the expression of GLT1 in astrocytes. This finding is consistent with previous reports that GLT1 is mainly expressed in astrocytes [ 25 , 26 ]. The co-localization was reduced by 55% ( p < 0.0001) in the Abeta group, 57% ( p < 0.0001) in the Glu group, and 69% ( p < 0.0001) in the Abeta + Glu group compared to the control group.…”
Section: Resultssupporting
confidence: 94%
“…Immunofluorescence staining showed abundant co-localization of GLT1 with GFAP in the control group, indicating the expression of GLT1 in astrocytes. This finding is consistent with previous reports that GLT1 is mainly expressed in astrocytes [ 25 , 26 ]. The co-localization was reduced by 55% ( p < 0.0001) in the Abeta group, 57% ( p < 0.0001) in the Glu group, and 69% ( p < 0.0001) in the Abeta + Glu group compared to the control group.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, double immuno uorescent staining showed that GLT1 expression in astrocytes in the neuron-astrocyte co-cultures signi cantly upregulated after the sulbactam incubation. This nding is consistent with previous reports that GLT1 primarily expresses on astrocytes [48,49], and sulbactam could dose dependently upregulate GLT1 expression [23,24,50,51]. In addition, the present study also showed that GLT1 co-localized abundantly with neuronal marker MAP2 in the neuron-astrocyte co-cultures after sulbactam treatment, which meant that GLT1 expressed on neurons and its expression was upregulated by sulbactam as well.…”
Section: Discussionsupporting
confidence: 93%
“…Immuno uorescence stain showed abundant co-localization of GLT1 with GFAP in the control group, indicating the expression of GLT1 in astrocytes. This nding is consistent with previous reports that GLT1 mainly expresses in astrocytes [48,49]. The co-localization was reduced by 55% (P<0.0001) in the Abeta group, 57% (P<0.0001) in the Glu group and 69% (P = 0.0001) in the Abeta + Glu group compared to the control group.…”
Section: Glt1 Expressionsupporting
confidence: 93%
“…Glutamate is primarily transported by excitatory amino acid transporter 2 (EAAT2), which is the primary mechanism for maintaining extracellular glutamate concentrations in the CNS below excitotoxic levels. 45 Neuroprotection is mediated by EAAT2. The PPARγ transcription factor is ligand-dependent and responds both to chemical and physiological signals.…”
Section: Effects Of Yp-7 On Excitotoxicity To the Primary Cultured Hi...mentioning
confidence: 99%